Support for Collective Entrepreneurship Among Indigenous Youth: An Account of an Experience of Indigenization - Fortin-Lefebvre, Emilie; Awashish, Karine; Blanchet-Cohen, Natasha (Canadian Journal of Nonprofit and Social Economy Research, 2023)
This article focuses on how to re-“concile” support for entrepreneurship in an Indigenous context based on the case study of StartUp Nations, a collective entrepreneurship support program for First Nations youth in Quebec. Based on a decolonial qualitative approach allowing the valorization of people’s points of view according to their own cultural framework, this article shows how the pedagogical approach and the theoretical content of the program have been adapted. The actions of re-“conciliation” can be summarized in six actions taken by StartUp Nations to respond to the needs and aspirations of young people, as well as to the realities of First Nations. Cet article s’intéresse à la manière de ré-« concilier » l’appui à l’entrepreneuriat en contexte autochtone à partir de l’étude du cas de StartUp Nations, un programme d’accompagnement en entrepreneuriat collectif pour les jeunes des Premières Nations au Québec. Basé sur une approche qualitative décoloniale permettant la mise en valeur de points de vue des personnes selon leur propre cadre culturel, cet article montre comment l’approche pédagogique et le contenu théorique du programme ont été adaptés. La démarche de ré-« conciliation » peut être résumée en six actions concrètes prises par StartUp Nations pour répondre aux besoins et aspirations des jeunes, ainsi qu’aux réalités des Premières Nations.